DO STORY TELLING TECHNIQUE ON HELPS STUDENTS’ SPEAKING ACHIEVEMENT?: AN EXPERIMENTAL STUDY OF EIGHT GRADE - Fajar Tri Wahyudi (Graduate Program, University of Islam Malang, 2020)
This research was aimed at knowing the effectiveness of using storytelling technique in teaching speaking ability. The research question as follow; 1)Is there any significant difference of students’ speaking ability that are technique by using storytelling and role play?, 2) Is there any significant of storytelling technique on the students speaking ability? To answer that question the researcher applied storytelling technique for speaking ability to eight grade junior high school.This research is an experimental research. The instrument was used in this research was pretest and posttest. The students were taken from eight grade junior high school which is consist of two classes. It started by giving pretest, to know the students speaking ability. Then the researcher found two classes with the equal mean score as the research sample. The researcher divided them into experimental and control group. The research is done with pretest and posttest. Where the experimental group was A class which consist of 30 students and the control group was B class which consist of 30 students.The result of data analysis is taken from t observation that is 20.826 with significance level is .000. It can be concluded that the hypothesis of the research is accepted. The writer concludes that there is significant the influence of using storytelling technique on the students’ speaking achievement of grade eight.Keywords: Speaking achievement, Storytelling technique, Narrative text